The effect of temperature and particles concentration on the determination of thermo and physical properties of SWCNT-nanorefrigerant - Alawi, Omer A. (Elsevier Ltd, 2015)
Nanorefrigerants have the potential to enhance the heat transfer performances of refrigeration and air-conditioning systems. The current study investigates the thermophysical properties and heat transfer performance of Single Walled Carbon Nanotube (SWCNT) nanoparticles suspended in 1, 1, 1, 2-tetrafluoroethane (R-134a). Suitable models from existing studies have been used to determine the thermal conductivity and viscosity of the nanorefrigerants for the nanoparticle concentrations of (1 to 5. vol.%) at temperature of (300 to 320. K). The observation results show that, the thermal conductivity and specific heat of SWCNT/R-134a nanorefrigerant increased with the augmentation of particle concentrations and temperatures. Moreover, the results of viscosity and density of the nanorefrigerant show a significant increase with the increase of volume fractions. However, these parameters decreased accordingly with the increment of temperature. Therefore, optimal particle volume fraction is important to be considered in producing nanorefrigerants that can enhance the performance of refrigeration systems.